Dynamic photovoltaic greenhouse: Energy efficiency in clear sky conditions. (15th May 2016) - Marucci, Alvaro; Cappuccini, Andrea
Highlights: A prototype of dynamic photovoltaic greenhouse was studied. The photovoltaic production and the microclimate inside the structure was studied. Different shading percentages on days with completely clear sky was analyzed. Reflective aluminum panels allow to recover the solar radiation lost by reflection. The constantly panel's rotation allows to adjust the shading degree. Abstract: This paper assesses the energy efficiency of a prototype of a dynamic photovoltaic (PV) greenhouse that has an asymmetric cross section and allows the rotation of the PV modules around their longitudinal axis throughout the day to select the degree of shading inside the structure. The goal of this research is to study the production of energy and the microclimate inside the structure with different tilt angles of the PV panels to improve the information available to support the farmers and to create a PV greenhouse capable of producing income from electrical and agricultural activity. The average values of the internal air temperature and relative humidity, measured during the hottest period and on days with clear skies, are within the optimal ranges for major vegetable species (17–27 °C and 60–90%, respectively). The values of the solar radiation available for the plants were always sufficient for normal agricultural operations, except for the last two days of the experiment (values lower than 5 MJ m −2 ) in which the shading percentage analyzed was too high for normal production. When the shading percentage was highest (78%), the maximum value of PV power (102 W m −2 ) was recorded and when the shading percentage was equal to 0%, the minimum value of PV power (20 W m −2 ) was recorded. The results show that it is possible to balance the electricity production using photovoltaic panels and the agricultural production as a function of the type of crop grown, latitude, operating season, and characteristics of the greenhouse.